Municipal Public Transport Line Modelling - Jelinek, Jiri (Communications - Scientific letters of the University of Zilina, 2014)
This contribution deals with modelling and simulation of a transport system of a public transport line as one of the ways leading to deeper insight into the system and thus also to its development and its quality and effectiveness improvement. Professional software for simulation model creation was used for implementation of the model. Questions related to accessibility of real data for the model setting and their processing will also be discussed.